UN Women's Diplomacy Strategy to Influence Indian Government Policy to Eradicate Widow Stereotyping - Dandi, Muh. Zulhamdi Suhafid; Putri , Aulia Nabilah Syah (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
This research analyzes UN Women's diplomatic strategy in influencing Indian government policy to eliminate stereotypes and discrimination against widows. With the increasing population of widows, India faces serious challenges related to the systemic marginalization of widows, including social exclusion, economic impoverishment, and cultural oppression. Using Clive Archer's theoretical framework on international organizations, this research explores UN Women's role as an instrument, arena, and actor in efforts to drive policy change in India. The research method used is qualitative with data collection techniques through journals and reports related to UN Women's diplomacy strategy in influencing Indian government policies to alleviate widow stereotypes in India. The results showed that the effectiveness of UN Women's diplomacy strategy relied heavily on its ability to build local legitimacy through partnerships with civil society organizations and adaptation of programs to the local cultural context. The research also identified that a multi-level approach that combines formal diplomacy with grassroots programs provides more optimal results in influencing policy change. These findings make an important contribution to the understanding of how international organizations can effectively influence national policy change on issues that have deep cultural roots.